Ocular surface disorders and its associated factors among Intensive Care Unit patients - Hamid, Abbas Abd (2022)
Introduction Patients in Intensive Care Unit are at increased risk of ocular surface disorders. Objective To determine the prevalence and its associated factors of ocular surface disorders in intensive care units. Methodology A cross sectional study was conducted from November 2020 until December 2021 involving 166 patients in Intensive Care Unit, Hospital Selayang and Hospital Universiti Sains Malaysia. Exclusion criteria includes facial trauma involving orbital region, usage of topical medication and any pre-existing anterior segment ocular pathologies. Diagnosis made based on clinical assessments from tear break up time, corneal fluorescein stain and Schirmer’s test. Factors related to ocular surface disorders were assessed. Statistical analysis of simple and multiple logistic regression was performed using SPSS Inc version 26. Result A total of 166 patients were enrolled in this study. The mean age was 51.8 ± 14.32. The mean length of stay in the ICU was 11.5 ± 9.31 days. One hundred and thirty-five patients (81%) required ventilation, 114 (68.7%) required sedation and 67 (40.4%) required inotropes. Lagophthalmos was identified in 49 patients (29.5%). The prevalence of ocular surface disorders in the Intensive Care Unit patients was 63.3%. The following odds ratios (95% confidence intervals) for ocular surface disorders were estimated using the multiple logistic regression model: female: 5.97 (1.18, 30.22) and length of ICU stay: 2.58. (1.84, 33.63). Conclusion Ocular surface disorders are common in Intensive Care Unit patients. The prevalence is 63.3%. The most important associated risk factors that predispose to ocular surface disease were female gender and length of Intensive Care Unit hospitalisation.